نحو مدرسة أنثروبولوجية لدراسةالمجتمعات في المنطقةالعربية - شناق, محمد سليمان (Changement Social, 2018)
This paperwillpresent an intellectualattemptbased on the reality in whichwe live in the Arabregion, withoutseparating or departingfrom the prevailinganthropologicaltheory in thisfield of knowledge, and not isolating the Arabsocieties in a unique and isolatedsense of the world'santhropological and anthropologicalheritage. In the expression, discussion and study of issues of particularAraboriginstemmingfrom the historicalheritage, religious and humanitarian, whichinhabit the regionwithvarious components expressed by the culture of thisregion.